The Use Of Role Play Method To Improve English Speaking Skills Of Students Majoring In Spa Therapist Venus One Tourism Academy - Kembariasih, Desak Ayu; Adiwijaya, Pande Agus; Numertayasa, I Wayan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
There are still many students who have difficulty in speaking English due to lack of confidence, lack of practice opportunities, and learning approaches that are less contextual and interactive. The learning method used is the role play method, which can simulate workplace situations directly and allow students to learn in a real context. This study aims to explore the effectiveness of role play method in improving English speaking skills among students majoring in SPA Therapist at Venus One Tourism Academy. The study was conducted in two cycles using a Classroom Action Research (CAI) design. The research subjects consisted of eight students who faced difficulties in speaking skills. Data were collected through pre-test, post-test, observation, and documentation. The pre-test results showed that the average score of students' speaking skills was in the low category, which was 50. After applying the role-playing method, the post-test results showed a significant improvement, with the average score reaching 82.4, in which 87.5% of students managed to meet the Minimum Completion Criteria (KKM) set. The findings show that the application of the role-play method effectively increased students' motivation, participation, and confidence in speaking English. This study recommends the use of the role method as a teaching strategy that can be adopted by educators in language education, especially in the context of vocational education in the tourism industry.